Radio-interferometric tracking using fault-tolerant phase unwrapping. (9th March 2016) - Zachár, Gergely; Simon, Gyula
Abstract: A novel radio-interferometric measurement method for tracking applications is proposed. Fixed radio transceiver nodes are used to generate interferometric signals, allowing the tracking of a moving object equipped with a radio receiver. Low-frequency phase measurements of the interferometric signals are processed by the proposed simultaneous phase unwrapping algorithm, and then the real-time position estimates are calculated. The performance of the tracking system is analyzed by simulations and real measurements, indicating that the proposed method tolerates well substantial measurement phase noise and even sporadic large measurement errors.